1999
DOI: 10.1038/sj.bjc.6690394
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin 6 (IL-6) correlates with oestrogen receptor in human breast carcinoma

Abstract: Multifunctional cytokines play important and only partially defined roles in mammary tumour development and progression. Normal human mammary epithelial cells constitutively produce interleukin 6 (IL-6), IL-8 and a non-secreted form of tumour necrosis factor. Transformation of mammary epithelial cells by different oncogenes is frequently associated with alterations of cytokine/growth factor production and responsiveness. In the present study we analysed the expression of IL-6 in 149 cases of invasive breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 20 publications
6
40
1
Order By: Relevance
“…On the contrary, other studies show that IL-8 expression in breast tumors is identical between normal and cancer tissues (Speirs et al, 1996). Interestingly, IL-6 expression has been correlated with ER status (Fontanini et al, 1999), which suggests that IL-6 and IL-8 are opposite markers.…”
Section: --------------------------------------------------------"mentioning
confidence: 62%
“…On the contrary, other studies show that IL-8 expression in breast tumors is identical between normal and cancer tissues (Speirs et al, 1996). Interestingly, IL-6 expression has been correlated with ER status (Fontanini et al, 1999), which suggests that IL-6 and IL-8 are opposite markers.…”
Section: --------------------------------------------------------"mentioning
confidence: 62%
“…This suggests that, apart from the regulatory effects of IL-6 on VEGF production, other mechanisms are responsible for the deleterious effects of high serum IL-6 levels on tumour growth, thus explaining their strong correlation with prognosis in metastatic breast cancer patients. Although IL-6 expression in early-stage breast carcinomas has been correlated with low grade, oestrogen receptor status and good prognosis (Fontanini et al, 1999;Karczewska et al, 2000), several studies have shown that IL-6 may contribute to disease progression, particularly in advanced breast cancer patients. Indeed, IL-6 can modulate steroid hormone responsiveness by increasing aromatase activity and oestradiol 17 beta-hydroxysteroid dehydrogenase activity in malignant tissue and by activating oestrogen receptor-a (Duncan et al, 1994;Singh et al, 1999;Speirs et al, 2000).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%
“…Sections were scored independently by two pathologists (F B and L P) using a method described previously (25): the intensity of staining was scored from 0 to 3 (0=absent; 1=weak; 2=moderate and 3=strong); the proportion of malignant cells positively stained was scored from 0 to 4 (0=no positive cells; 1 # 10% positive cells; 2 11±50%; 3 51±75% and 4 76±100%). The two scores were added to yield the total score (0±7).…”
Section: Immunohistochemistrymentioning
confidence: 99%